Caribbean Report 15-03-1993 - Rowe, Yvette (anchor); Baptiste, Sandra (correspondent); Sandiford, Erskine (interviewee); MacDonald, Ian (interviewee); Allen, Gary (correspondent); Martin, Lionel (correspondent); Sandiford, Erskine (interviewee) (The British Broadcasting Corporation, 1993)
Barbados Prime Minister - Erskine Sandiford has announced a proposal for a wage freeze throughout the country in both public and private sectors including statutory corporations for a period of two years – correspondent Sandra Baptiste reports. The first budget presented by Asgar Ally – Guyana’s Fiannce Minister of Guyana’s newly elected Progressive Party/Civic (PPP/C) is being assessed - correspondent, Ian Mac Donald gives an analysis on the budget. As election campaigning heightens in Jamaica there are concerns about elections violence in Jamaica - correspondent Gary Allen reports on the politically related violence rising out of the election campaigns. The Cuban economy has taken another battering from the forces of nature (hurricane) – people were killed and crops were extensively damaged. Armed forces and the essential services have been working around the clock - correspondent Lionel Martin from Havana. A concession has been granted to opponents of the British Government’s plan to tighten immigration laws. The asylum bill would remove the right of appeal for visitors refused entrance into Britain. The Bill is aimed at cracking down on bogus asylum applications, and will return to the House of Commons for consideration before becoming law.
Headlines with anchor Yvette Rowe (00:00-00:24).
1. Barbados Prime Minister - Erskine Sandiford has announced a proposal for a wage freeze throughout the country in both public and private sectors including statutory corporations for a period of two years (00:25-04:48).
2. The first budget presented by Asgar Ally – Guyana’s Fiannce Minister of Guyana’s newly elected Progressive Party/Civic (PPP/C) is being assessed (04:49 – 06:47).
3. As election campaigning heightens in Jamaica there are concerns about elections violence in Jamaica (06:48 -11:00).
Keywords: Wages and labor productivity--Barbados.; Politics and government--Barbados.; Labor-- Barbados.; Budget – Guyana.; Budget statement -- Guyana.; Elections--Jamaica.; Elections -- Corrupt practices -- Jamaica.; Hurricanes--Cuba.; Economics--Cuba.; Great Britain--Emigration and immigration.; Great Britain--Politics and government.; Great Britain--Social conditions--21st century.; Caribbean Area--Emigration and immigration.